Facile fabrication of nano zerovalent iron and granular activated carbon for enhanced nitrate removal from water - Nafeesa Aman; Nimrah Ijaz; Irum Fatima; Muhammad Usman Farid; Haroon Rashid; Asif Ayub; Dhay Ali Sabur; Israa Taha Ibrahim; Hany M. Abd El-Lateef; Iram Rafique; Yasir Mehmood; Rasha M. K. Mohamed (Geology, Ecology, and Landscapes)
Nitrate contamination of groundwater has become a serious threat to the environmental health. In this study, nano zerovalent iron (nZVI) and granular activated carbon (GAC) were fabricated and characterized by some advanced analytical techniques including SEM, BET, XRD, and FTIR to investigate their structural properties. Batch experiments were conducted for the adsorption of nitrate from water. The effect of various parameters including pH, adsorbent dose, initial nitrate concentration, and contact time was investigated. The nZVI showed maximum adsorption capacity (qmax) of 104.20 mg/g for nitrate at optimum conditions (pH 2, initial concentration 50 ppm, adsorbent dose 3.75 g/L at room temperature), while GAC has shown qmax 81.07 mg/g at optimum conditions (pH 6, initial concentration 50 ppm, adsorbent dose 3.75 g/L at room temperature). Equilibrium data of nitrate adsorption by nZVI and GAC followed the Langmuir isotherm (R2 = 0.999) and pseudo-second-order kinetic model. ANOVA and RCBD approaches were used to evaluate and check the significant level of various parameters.